Mechanistic insights into Cu and K promoted Fe-catalyzed production of liquid hydrocarbons via CO2 hydrogenation. (December 2019) - Hwang, Sun-Mi; Han, Seung Ju; Min, Ji Eun; Park, Hae-Gu; Jun, Ki-Won; Kim, Seok Ki
Graphical abstract: Highlights: Fe lattice expansion was observed by incorporation of Cu. Cu reduced O removal energy and accelerated CO2 conversion rate. K helped formation of Fe-Cu phase as an active site during the reaction. K selectively decreased H affinity for C and increased chain growth probability. Abstract: Understanding the origin of the high activity of Fe-Cu-K catalysts during CO2 hydrogenation for liquid hydrocarbon production is imperative. However, designing suitable catalysts for efficient power-to-liquid processes remains challenging. In this work, we determined how Cu and K modified the Fe structure and revealed the origin of their synergistic effect in promoting its catalytic performance during CO2 hydrogenation to long-chain hydrocarbons. Detailed analyses confirmed that K addition facilitated incorporation of Cu into the Fe bulk lattice and helped maintain either a metallic or carbide active phase during the reaction. Electronic structure calculations suggested that formation of Fe-Cu alloy facilitated CO2 hydrogenation, regardless of the reaction pathway. A series of scaling relations between C binding energies and other adsorbates suggested that the presence of K facilitated CO formation and C–C coupling reactions over the Cu and Fe driven catalysis, respectively. Hence, the coexistence of Cu and K in the Fe catalyst is essential for producing liquid hydrocarbons from CO2 .